Efficient degradation of Acid Orange 7 in aqueous solution by iron ore tailing Fenton-like process. (May 2016) - Zheng, Jianming; Gao, Zhanqi; He, Huan; Yang, Shaogui; Sun, Cheng
Abstract: An effective method based on iron ore tailing Fenton-like process was studied for removing an azo dye, Acid Orange 7 (AO7) in aqueous solution. Five tailings were characterized by X-ray fluorescence spectroscope (XFS), Brunner−Emmet−Teller (BET) measurement, and Scanning Electron Microscope (SEM). The result of XFS showed that Fe, Si and Ca were the most abundant elements and some toxic heavy metals were also present in the studied tailings. The result of BET analysis indicated that the studied tailings had very low surface areas (0.64–5.68 m 2  g −1 ). The degradation efficiencies of AO7 were positively correlated with the content of iron oxide and cupric oxide, and not related with the BET surface area of the tailings. The co-existing metal elements, particularly Cu, might accelerate the heterogeneous Fenton-like reaction. The effects of other parameters on heterogeneous Fenton-like degradation of AO7 by a converter slag iron tailing (tailing E) which contains highest iron oxide were also investigated. The tailing could be reused 10 times without significant decrease of the catalytic capacity. Very low amount of iron species and almost undetectable toxic elements were leached in the catalytic degradation of AO7 by the tailing E. The reaction products were identified by gas chromatography-mass spectrometry and a possible pathway of AO7 degradation was proposed. This study not only provides an effective method for removing azo dyes in polluted water by employing waste tailings as Fenton-like catalysts, but also uses waste tailings as the secondary resource. Graphical abstract: Highlights: The iron ore tailing was first applied as heterogeneous Fenton catalyst. Acid Orange 7 was oxidized completely within 60 min by using the tailing and H2 O2 . The mechanism of the tailing as an efficient heterogeneous Fenton catalyst has been explored. ·OH is the main active radicals for the Fenton-like reaction. The tailing can be reused more than nine times without apparent decrease of the catalytic capacity.